2014
DOI: 10.1088/1748-0221/9/08/t08005
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication study of GaAs mesa diodes for X-ray detection

Abstract: A study of leakage currents using GaAs mesa p-i-n diodes for X-ray photon counting is presented. Different wet chemical etching solution and etch depth were used in the fabrication of these mesa diodes. Low and uniform leakage currents were achieved when the diode fabrication used (i) a combination of main etching solution and finishing etching solution for the etching, and (ii) partially etched mesas. The diodes fabricated using these methods showed well-defined X-ray peaks when illuminated with an 55 Fe radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The thicker i layer of the presently reported devices, compared to previously reported thinner GaAs p þ -i-n þ mesa photodiodes, [15][16][17][18] resulted in higher quantum detection efficiency and improved energy resolution at the investigated temperature range. The improved energy resolution of the presently reported spectrometer was attributed to the reduced white series, 1/f, and dielectric noise, all depending upon the capacitance of the photodiode.…”
Section: B Noise Analysismentioning
confidence: 66%
See 2 more Smart Citations
“…The thicker i layer of the presently reported devices, compared to previously reported thinner GaAs p þ -i-n þ mesa photodiodes, [15][16][17][18] resulted in higher quantum detection efficiency and improved energy resolution at the investigated temperature range. The improved energy resolution of the presently reported spectrometer was attributed to the reduced white series, 1/f, and dielectric noise, all depending upon the capacitance of the photodiode.…”
Section: B Noise Analysismentioning
confidence: 66%
“…Although the spectrometers S1 and S2, employing the diodes, D1 and D2, respectively, had better energy resolution (FWHM at 5.9 keV) compared to previously reported thinner GaAs p þ -i-n þ mesa X-ray photodiodes, [15][16][17][18] further work is required to improve the FWHM to values close to the best results achieved with planar Schottky contact GaAs X-ray detectors at room temperature; 0.266 keV FWHM at 5.9 keV 12 and 0.300 keV FWHM at 5.9 keV. 14 Thicker devices would result in a lower capacitance, which has a direct effect in reducing the white series, 1/f, and dielectric noises.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The best energy resolution (FWHM at 5.9 keV) was achieved at 5 V reverse bias at each investigated temperature. It was measured to be 730 eV at 0 C, 750 eV at 20 C, 770 eV at 40 C, and 840 eV at 60 C. The other previously reported that 7 lm GaAs devices had an energy resolution of $1 keV at room temperature 14 and thinner GaAs p-i-n mesa photodiodes (2 lm) had $1keV FWHM at 60 C, 12 coupled to similar front-end electronics. The improving of the energy resolution was attributed to slightly lower electronic noise arising from the preamplifier in adittion to better electrical characteristics (leakage current and capacitance) of the detector compared to those previously reported.…”
Section: Noise Analysismentioning
confidence: 87%
“…13 A fabrication study of GaAs mesa photodiodes regarding the effects of the wet chemical etchants and etch depths on the dark currents has also been reported. 14 Room temperature results characterising two randomly selected fully etched 200 lm GaAs p þ -i-n þ mesa X-ray photodiodes with 7 lm thick i-layers have been previously presented. 15 Here, we report the electrical characterization of the same diodes at the temperature range 0 C to 120 C, and we present X-ray spectra accumulated with one of the diodes operated in the temperature range 0 Cto60 C.…”
Section: Introductionmentioning
confidence: 99%